The Association between Major Adverse Cardiovascular Events and Peripheral Artery Disease Burden - Niiranen, Oskari; Virtanen, Juha; Rantasalo, Ville; Ibrahim, Amer; Venermo, Maarit; Hakovirta, Harri (MPDI, 2025)
Objective: The aim of the present study was to investigate the possible relationship between the segmental burden of lower limb atherosclerosis and Major Adverse Cardiovascular Events (MACEs). Methods: All the consecutive symptomatic peripheral artery disease (PAD) patients admitted for digital subtraction angiography (DSA) at Turku University Hospital department of Vascular Surgery between 1 January 2009 and 30 July 2011 were retrospectively analyzed. Angiography due to symptomatic PAD was used as the index date for the inclusion in the study. The segmental burden of atherosclerosis based on DSA was divided into three categories according to the highest disease burden of the defined artery segment: aorto-iliac, femoropopliteal, or tibial segments. The major association for the study was MACEs (defined as a cerebrovascular event, heart failure (HF) and myocardial infarction requiring hospital admission). Demographic data and MACEs were obtained from the hospital electronic medical records system. Results. The lower limb atherosclerosis burden of tibial vessels was related to an increased probability for HF (OR 3.9; 95%CI 2.4–6.5) and for MACEs overall (OR 2.3; 95%CI 1.4–3.6). The probability of both HF and MACEs overall rose with the increasing severity of the atherosclerosis burden. Moreover, the more severe the tibial vessel atherosclerosis, the higher the risk of HF and MACEs. The most extensive tibial atherosclerosis patients had an OR 4.5; 95%CI 2.6–8.0 for HF and an OR 3.1; and 95%CI 1.7–5.6 for MACEs overall. The femoropopliteal disease burden was also associated with an increased risk of HF (OR 2.3; 95%CI 1.6–3.2) and MACE (OR 1.9; 95%CI 1.3–2.7). However, the increasing extent of atherosclerosis of the femoropopliteal segment solely increased the risk of MACEs. Conclusions: PAD patients with severe tibial atherosclerosis are likely to present with MACEs. The risk is further enhanced as the extent of tibial vessel atherosclerosis is increased. An association between MACE and severe atherosclerosis on the aortoiliac segment was not detected. However, when the femoropopliteal segment was the most affected artery segment, the risk of MACEs was increased.